The Use of Electrophoretic Isozymes to Detect Tungro Infected Rice - Suranto Suranto; Arief A.; Supyani Supyani (AGRIVITA, Journal of Agricultural Science, 2017)
Tungro is one of the most common diseases of rice plants which caused by double infection of RTBV (Rice Tungro Bacilliform Virus) and RTSV (Rice Tungro Spherical Virus), and it gives a significant economic loss. These viruses are transmitted by green leaf hopper (Nephottetix virescens. Distant), and the interaction between host plant and the viruses were still quite difficult to be fully understood. In order to look at whether there are any differences between the healthy and tungro infected rice, this study was set to examine the character differences between the infected and the healthy plants based on isozyme banding pattern. The infected plants were collected from three districts around Surakarta (Sragen, Sukoharjo, Klaten) followed by Polyacrilamide Gel Electrophoresis (PAGE) to evaluate the isozyme banding patterns. There were peroxidase, esterase and acid phosphotase isozymes used. The results showed that the real differences of isozyme banding patterns of both healthy and tungro infected plants were discovered. In all cases, the Tungro infected rice had thicker and more band numbers compared to the healthy one. This evident suggested that Tungro infected rice could be detected early using PAGE method.